Analisis Determinan Penghindaran Pajak dan Kualitas Audit sebagai Pemoderasi - Prasetiyo, Yudhi (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of profitability, firm size, and solvency on tax avoidance with audit quality as a moderating. Profitability used in this study is return on assets, solvency used in this study is debt to equity ratio. The method used is quantitative by analyzing the factors that influence tax avoidance by being strengthened or weakened by moderating variables, while the regression technique used is Regression Moderation Analysis in conducting statistical tests. The population in this study is the main sector of health companies listed on the Indonesia Stock Exchange (IDX) during 2018-2021, with sample criteria taken. The results of the study show that profitability as indicated in ROA, firm size, solvency as indicated in DER has no effect on tax avoidance. Then audit quality weakens the influence of ROA, firm size, DER on tax avoidance in the main sectors of health companies listed on the IDX for the 2018-2021 period.